That Our Children So May Grow : Imagining Legal Agency for Children - Van Praagh, Shauna; Ménard, Jean-Frédéric; Elsherif, Efat; Koper, Natalia (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 2023)
The authors invite innovative engagement with the notion and exercise of children’s agency through work situated within the context of the Children’s International Summer Villages camp and theoretically grounded in both childhood studies and critical legal pluralism. By exploring campers’ participation in activities infused with law-related issues, the paper suggests that children can be understood as creators of law and thus as significant legal agents.